HUBUNGAN POLA ASUH ORANG TUA DENGAN KEJADIAN STUNTING PADA BALITA USIA 24-59 BULAN DI DESA NAKAMURA KECAMATAN MOROTAI SELATAN KABUPATEN PULAU MOROTAI: The Correlation Between Parenting Style and Stunting in Toddlers Aged 24-59 Months in Nakamura Village, South Morotai, Morotai Island - Trilia Romadhona; Tutik Hidayati; Muthmainnah Zakiyyah (Forind Press, 2023)
Parenting styles are all forms and processes of interaction that occur between parents and children and can influence the development of a child's personality. Stunting, also known as “shortness